Pengaruh Penghindaran Pajak, Agresivitas Pajak, Risiko Pajak, dan Manajemen Laba Terhadap Risiko Perusahaan - Syanazka Zalyu Azzahra; Fatchan Achyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tax avoidance and tax aggressiveness are actions to reduce and manipulate the tax burden. This action is taken by many managers to maintain a good image of the company's financial statements. The existence of this tax avoidance and aggressiveness can create tax risks where this risk occurs due to the uncertainty of tax payments made by companies. This decision is not far from the action of profit management which is an activity of management intervention in the financial reporting process to external parties in order to achieve the company's profits. All of these activities can trigger company risks These corporate risks include various types of risks that occur in the company. This study aims to analyze the influence of tax avoidance, tax aggressiveness, tax risk, and earning management on corporate risk. In this study the population and research sample came from all manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period The study used a purposive sampling method with data from 46 companies so that the sample in this study amounted to 138 The testing method in this study uses multiple regression analysis The results of the study found empirical evidence that tax avoidance, tax aggressiveness, and earning management have no effect on corporate risk. Meanwhile, tax risk has an effect on the company's risk.